Study of simultaneous mass transfer and nucleation in cryogenic packed bed for the removal of CO2 from natural gas - Ali, A. (Trans Tech Publications Ltd, 2014)
The paper presents the concept of cryogenic growth kinetics during separation of CO2 from natural gas using Avrami nucleation model. The interface frost layer on the glass packing of cryogenic bed is assumed as germ nuclei. The bed porosity is considered time dependent. The expression for time varying bed porosity is derived based on Avrami model. The experimentation was conducted to validate the model and the resulting simulation studies show good resemblance with experimental results. Â© 2014 Trans Tech Publications, Switzerland.